2013
DOI: 10.1590/s1413-80502013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Impactos do Crédito Rural na produtividade da terra e do trabalho nas Regiões Brasileiras

Abstract: O objetivo deste trabalho é mensurar os impactos do crédito rural sobre a produtividade da terra e do trabalho nas grandes regiões brasileiras. A abordagem metodológica é baseada em modelo de restrição de crédito e no método do propensity score. Foram utilizados microdados do Censo Agropecuário de 2006. Os resultados mostram que o crédito não foi efetivo para aumentar a produtividade dos fatores no setor agrícola, exceto para a região nordeste do Brasil. Os resultados apontam para a necessidade de melhorias na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
5
0
6
Order By: Relevance
“…Our results complement and endorse other findings in the literature about rural credit policy, but with distinct scopes regarding crops, regions and categories. Concerning regional characteristics, according to Santos and Braga (2013), there was a very weak association between credit policy and agriculture's soil productivity, in Brazilian macro-regions in 2006. Oliveira et al (2008) also found no influence of rural credit for sugarcane and corn crops for Pronaf category in Northeastern Brazil.…”
Section: Variables and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Our results complement and endorse other findings in the literature about rural credit policy, but with distinct scopes regarding crops, regions and categories. Concerning regional characteristics, according to Santos and Braga (2013), there was a very weak association between credit policy and agriculture's soil productivity, in Brazilian macro-regions in 2006. Oliveira et al (2008) also found no influence of rural credit for sugarcane and corn crops for Pronaf category in Northeastern Brazil.…”
Section: Variables and Datamentioning
confidence: 99%
“…Some studies argue that credit constraints may reduce market efficiency (Guirkinger et al, 2007) and the agricultural supply (Briggeman et al, 2009). However, considerable literature also present mixed results from the credit policy and questions its potential to enhance agricultural productivity and production (Ciaian et al, 2012;Gasques et al, 2012Gasques et al, , 2017Santos and Braga, 2013;Turvey, 2013). Constrained or unequal access to credit might not only reduce its effectiveness, but also reinforce market imperfections, such as capital concentration and additional technological restrictions (Alves et al, 2013;Guasch and Braverman, 1986;Hoffmann and Kassouf, 1989;Turvey, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Como discutimos na seção 2 do presente artigo, o financiamento da atividade rural é liderado pelo setor público e os subsídios foram essenciais para os ganhos de produtividade e modernização da agropecuária no Brasil (Belik, 2014;Araújo, 2011;Santos & Braga, 2013). No entanto, o mercado de cré-dito rural, altamente regulamentado, parece apresentar falhas advindas das constantes renegociações da dívida rural que privilegiam tipos de mutuários e possuem regras que estimulam o não pagamento da dívida rural.…”
Section: Conclusõesunclassified
“…Aos agricultores que dele se beneficiaram, os estímulos do cré-dito rural facultaram uma dianteira no processo de modernização e um crescente distanciamento daqueles que, alijados dessa e de outras políticas, mantiveram-se em sistemas produtivos tradicionais (SZMRECSÁNYI e RAMOS, 2002). Santos e Braga (2013) ressaltam que, nas déca-das de 1970 e 1980, a distribuição do crédito se deu em função do tamanho dos estabelecimentos dos tomadores, o que favoreceu grandes proprietários. Não podendo oferecer garantias, os menores estabelecimentos se viram diante de barreiras que terminaram por lhes impor restrições de acesso ao crédito.…”
Section: Introductionunclassified
“…Conforme Santos e Braga (2013), como a taxa de juros no mercado de crédito rural tem sido fixada abaixo do ponto de equilíbrio, o problema posto ao intermediário financeiro é a minimização de seus custos. Diante disso, os problemas de informação tornam-se relevantes.…”
Section: Introductionunclassified